Cobalt-catalyzed reductive dimerization of enone and manganese-catalyzed ring open coupling of cyclopropanol with enone - Zhang, Yonghui (2018)
The radical reaction has been widely applied in organic chemistry. Radical reactions, for the specific property, gained great attention. Numerous achievements have been gained in this field. The radical initiator could come from a very wild source. Typically, the illumination, trans-metal catalysts, halogen molecules, azo compounds, and organic and inorganic peroxides could all play the role of radical initiator. Among these reactions, the radical mediated C=C bond activation and C-C bond coupling reaction have taken an important position in organic synthesis. The olefin is a kind of common organic species. The special structure and electronic property of olefin give rise to high reactivity, which leads to the wild reaction types and the various regioselective and stereoselective structure of the products. It was very common to find C=C bond structure involved in polymerization, addition, substitution oxidation and reduction reaction. Among these reactions, the coupling of olefin plays an important role in chemistry research. The cycloalkanes generally keep stable structure in organic reaction as the C-C single bond. However, when number of carbon consisting the ring becomes less, the bond angles between C-C bond would decreases. At the same time, the ring strains would rise significantly which would lead to much higher reactivity. In most conditions, the small cycloalkane, especially cyclopropane and analogues, would undergo a ring open progress in organic reactions. The cyclopropanol contains the main properties of cyclopropane. The reaction property of cyclopropanol is to some extent similar with enone. These characters indicate the special reactivity and potential application in organic synthesis. Particularly, the author firstly would like to present a dimerization of enone. The C=C bond of would go through a reductive coupling progress with Cobalt(II) catalyst in mild condition. The reaction could provide dione product at good to excellent yield. Then, a ring open coupling of cyclopropanol with enone was conducted. The Manganese catalyst was selected to perform this reaction, and as a result, various dione products would be obtained at excellent yield in a simple method.